THE IMPROVING OF MICROBIOLOGICAL SAFETY OF BREAD FROM DISPERSED WHEAT GRAIN - Oksana Anatolievna Markitanova; Valentina Danilovna Malkina; Hachatur Alexandrovich Baluyan; Elena Vladimirovna Zhirkova; Vladimir Viktorovich Martirosyan (Современная наука и инновации)
The technological solutions to reduce the qualitative and quantitative composition of microflora of dispersed grain mass, consisting in soaking the grain in the presence of acids (sorbic or benzoic or citric acid), which reduces the contamination of grains and content of extraneous microflora in ready grain bread.